(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
The method of geophysical monitoring of Earth crust was applied, which allows to fulfill the monitoring of modern geodynamic processes of Armenia through geodynamic observations, observations of geochemistry of groundwater, vector module of magnetic field and seismic mode of the region. The distribution of hydrogeodynamic processes in time and space is observed. The character of space-time distribution of geodynamic stress is defined.